Tekno Ekonomi Produksi Perekat Aqueous Polymer Isocyanate Berbasis Lateks Karet Alam (Techno-Economic of Natural Rubber Latex-Based Aqueous Polymer Isocyanate Adhesive) - Fahriya Puspita Sari; Widya Fatriasari; Raden BP Laksana; Teguh Darmawan; Jayadi Jayadi; Euis Hermiati (Masyarakat Peneliti Kayu Indonesia, 2016)
Natural rubber latex (NRL)-based aqueous polymer isocyanate (API) adhesive can potentially be used for the production of wood panels or composites. Bonding properties of the adhesive could meet the standard of the wood panels produced. In order to complete its assessment as a commercial wood adhesive, it is important to conduct a techno-economic analysis of this adhesive. The design and analyses were based on 100 L production capacity. The techno-economic analysis as a basis value of the investment to be incurred in the API adhesive production considered the capability of design tools during the production process. Based on the analysis, to produce API adhesives by 34.8 tons per year it is required an investment of 509.5 million rupiahs. The production cost of API adhesives for Rp 50.000 kg-1 is Rp 35.798 with assuming a sales profit of 21.30%. The payback period is 1 year with shut down point (SDP) of 14%, and the break-even point (BEP) of 20.51%. The analysis at various production capacities (34.8, 50, 75, and 100 tons year-1) indicated that API adhesive production will be more profitable with greater production capacity because it can shorten the payback period and increase the return on investment.Keywords: API adhesives, low temperature setting, natural rubber latex (NRL), production design, techno-economic